2019 IEEE 2nd 5G World Forum (5GWF) 2019
DOI: 10.1109/5gwf.2019.8911613
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Fiber and mmWave Wireless Convergence for 5G Fronthaul Networks

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nonetheless, the value of R and C change with the given active area. For example, for an active area of 1.68 um 2 modulator offers a large bandwidth (78.3 GHz) with power consumption below 10 fJ per bit. For 25% of graphene, the modulator has an active area of 1.68 µm 2 whereas with 100% graphene, the modulator occupies 6.72 µm 2 .…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the value of R and C change with the given active area. For example, for an active area of 1.68 um 2 modulator offers a large bandwidth (78.3 GHz) with power consumption below 10 fJ per bit. For 25% of graphene, the modulator has an active area of 1.68 µm 2 whereas with 100% graphene, the modulator occupies 6.72 µm 2 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It should be further noted that the loss related to the ring's curvature as well as the graphene optical absorption are taken into account for the device's optimization by considering gap values satisfying the modulator's critical coupling condition. Moreover, the graphene's permittivity is obtained via the Kubo's formula [32], by substituting the results of its conductivity (for T = 300 K and Γ = 0.43 meV) into (2). Finally, we use the experimental values obtained from [35][36][37] for the refractive indexes of silicon, silica and alumina.…”
Section: Design and Properties Of The Optical Modulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising transmission type is a link based on optical fiber that offers high bandwidth, robustness to electromagnetic interference, and low latency (Gangwar & Sharma, 2012). For cellular applications, it is potential for improved performance by applying wavelengthdense multiplexing and radio over fiber (RoF) with millimeter wave (Pandey et al, 2021;Raddo et al, 2019;Rommel et al, 2019Rommel et al, , 2020 The speed and high radio frequencies of radio over fiber with millimeter wave to develop a transmission link has offered milestones in high data transmission rates (Li et al, 2020). However, the previous research showed that the received power level is still above the sensitivity of optical detectors with the determined length applications of 5G fronthaul purposes; therefore, the data quality should be improved to comply with 5G standards (Nugroho et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…e RoF network system is a potential solution to increase the capacity and mobility of access networks and could also reduce the cost of access networks. And the current advanced mobile communication 5G and the future 6G technologies are all based on this technology [4]. e basic principle of RoF technology mainly consists of three parts: central stations (CSs), optical fiber, and base stations (BSs) [5].…”
Section: Introductionmentioning
confidence: 99%